2009
DOI: 10.1021/ja807566t
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intramolecular [4 + 3] Cycloadditions Using Epoxy Enol Silanes As Functionalized Oxyallyl Cation Precursors

Abstract: Using epoxy enol triethylsilanes as oxyallyl cation precursors, [4 + 3] cycloadditions with various dienes occur under catalysis by silyl triflates and acids in good yields. The intramolecular [4 + 3] cycloaddition proceeds under mild conditions and generate hydroxylated cycloadducts with high diastereoselectivity and yields. Enantiomerically pure epoxy enol silanes have been shown to give excellent yields of the optically pure cycloadduct bearing multiple stereocenters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…Our studies of this cycloaddition showed that it was both high‐yielding and diastereoselective for the synthesis of carbobicyclic [5.4.0] systems (Scheme ) 8a. Substituents at various positions are compatible, and the absolute stereochemistry of the epoxide determined the facial selectivity of the cycloaddition.…”
Section: Desymmetrizing Reduction Of 4[a]mentioning
confidence: 95%
See 1 more Smart Citation
“…Our studies of this cycloaddition showed that it was both high‐yielding and diastereoselective for the synthesis of carbobicyclic [5.4.0] systems (Scheme ) 8a. Substituents at various positions are compatible, and the absolute stereochemistry of the epoxide determined the facial selectivity of the cycloaddition.…”
Section: Desymmetrizing Reduction Of 4[a]mentioning
confidence: 95%
“…[4h, 5d, 6f-h] Following our first work on ap artial structure, [6k] herein we report the asymmetric formal total synthesis of cortistatins A( 1)a nd J (2), intercepting advanced intermediates in the Nicolaou-Chen total synthesis [4c-d] and the Yamashita-Hirama total synthesis. [4g] This approach featured ahighly diastereoselectiveintramolecular [4+ +3] cycloaddition of epoxy enolsilanesw ith furan, ar eaction developed in our group, to construct the key oxygenbridged ring Bc oncomitantly with ring C. [7,8] Our synthesis of key cycloaddition precursor 11 commenced from the commercially available cyclopentanedione 4,w hich is destined to be ring Do fc ortistatins Aa nd J, and to serve as the chiral linker to unite the diene and the dienophile for the key intramolecular [4+ +3] cycloaddition. An umber of reactions were examined to achievethe desymmetrizing reduction of cyclopentanedione 4,i ncluding aC BS-reduction, [6k] but asymmetric transfer hydrogenation was ultimately found to be the most robust transformation for scale-up.…”
mentioning
confidence: 99%
“…Professor Chiu has designed a very clever system to form fused ring oxatropane products from electron-rich vinyl oxiranes tethered to furans (Scheme 28) [42]. This approach proceeds via an oxyallyl cation, which engages in an [4+3] cycloaddition with the furan moiety.…”
Section: Other Ring Expansions Of Oxiranesmentioning
confidence: 99%
“…The [4 þ 3] cycloaddition of furans with epoxy enol silane derived oxyallyl cations (Scheme 6.117) has been rendered a viable process by optimization of the reaction conditions and use of a bulky triethylsilyl group [233]. Dioxines were used as oxyallyl cation equivalents in a Au/Ag-catalyzed [4 þ 3] cycloaddition with furan [234].…”
Section: Additional Syntheses Of Furansmentioning
confidence: 99%